CMCpy: Genetic Code-Message Coevolution Models in Python. (January 2013) - Becich, Peter J.; Stark, Brian P.; Bhat, Harish S.; Ardell, David H.
Code-message coevolution (CMC) models represent coevolution of a genetic code and a population of protein-coding genes ("messages")- Formally, CMC models are sets of quasispecies coupled together for fitness through a shared genetic code. Although CMC models display plausible explanations for the origin of multiple genetic code traits by natural selection, useful modern implementations of CMC models are not currently available. To meet this need we present CMCpy, an object-oriented Python API and command-line executable front-end that can reproduce all published results of CMC models. CMCpy implements multiple solvers for leading eigenpairs of quasispecies models. We also present novel analytical results that extend and generalize applications of perturbation theory to quasispecies models and pioneer the application of a homotopy method for quasispecies with non-unique maximally fit genotypes. Our results therefore facilitate the computational and analytical study of a variety of evolutionary systems. CMCpy is free open-source software available fromhttp://pypi.python.org/pypi/CMCpy/ .